Effects of Water Regimes on Methane Emissions in Peatland and Gley Marsh. Issue 1 (24th May 2018) - Zhu, Xiaoyan; Song, Changchun; Chen, Weiwei; Zhang, Xinhou; Tao, Baoxian
Abstract : Core Ideas: Large pulses of CH4 can be emitted during short‐duration drying–wetting episodes. Peatland soils had higher CH4 emissions than gley marsh soils under a steady water table. Accurate CH4 estimates should include weather events that cause rapid changes in soil moisture regimes. The increasing frequency of extreme drought and intense precipitation events with global warming may affect CH4 emissions from different types of wetlands by regulating drying–wetting cycles. To determine the effects of different water regimes on CH4 emissions, a mesocosm experiment was conducted. Soil cores sampled from peatland and gley marsh were subjected to two drying–wetting cycles (i.e., fluctuating between −10 and 10 cm for 7 and 15 d, respectively) and three steady water table treatments (10, 0, and −10 cm). Alternation between drying and wetting stimulated CH4 emissions ( F = 16.03 for 7 d and F = 31.85 for 15 d, P < 0.01). The highest emission pulses were observed between 4 and 9 d after the water table increased according to the models. Peak pulse emissions significantly increased by 41% in peatland and 109% in gley marsh after rewetting compared with that in the steady 0‐cm water table treatment. Peatland soils had higher CH4 emissions than gley marsh soils under steady water table treatments ( P < 0.01). This study shows that large pulses of CH4 can be emitted during short‐duration drying–wetting episodes. If these pulses are not accounted for in budgets, CH4 emissions may be incorrectly assessed when comparing with field measurements during regularly spaced sampling intervals over only a few days or weeks by the static opaque chamber technique. Accurate estimates of CH4 budgets not only depend on increased measurement frequency but by necessity should incorporate weather events that cause rapid changes in the soil moisture regime.